The untapped potential of radiation and immunotherapy for hormone receptor-positive breast cancer - Matthew Fenton; Miki Yoneyama; Erik Wennerberg; Tom Lund; Andrew Tutt; Alan Melcher; Sandra Demaria; Navita Somaiah (npj Breast Cancer)
Abstract Hormone receptor-positive breast cancers are a diverse group of tumours, with only some responding well to immunotherapy. Alternative combination strategies such as radiotherapy present an exciting opportunity to improve immunotherapy responses. We review an intriguing overlap between the impact of oestrogen signalling and radiation on multiple signalling pathways and immune cells that may be exploited for therapeutic gains in breast cancer. This is synthesised with the pre-clinical data and clinical trial landscape supporting the use of combined radiation and immunotherapy to derive insights for future neo-adjuvant trial design.